PENGARUH PENGALAMAN PELANGGAN, KOMUNIKASI PEMASARAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS MEREK PADA RESTORAN MERAH PUTIH PURWOKERTO - Fajarsunarimo, Yanuar (Performance, 2014)
The purpose of this research is analyzing the impact of customer experience, marketing communication and customer satisfaction to brand loyalty. Customer experience and customer satisfaction has a significant influence on brand loyalty. Based on the previous studies, there is other factor that could affect the brand loyalty namely marketing communications. With the implementation of the concept of customer experience, marketing communications and customer satisfaction, customers will become loyal. The results of this study is there is influence of the customer experience on brand loyalty in Merah Putih restaurant shown with asign value at 0.008, there was no effect of marketing communication on brand loyalty shown with a sign value at 0.968. And there is influence of the customer satisfaction on brand loyalty in Merah Putih restaurant shown with asign value at 0.021. Apparently, the marketing communication which is run by Merah Putih restaurant is not maximized, it causes brand loyalty in Merah Putih restaurant become weak